Rapid microwave synthesis of magnetocaloric Ni–Mn–Sn Heusler compounds. (February 2020) - Trombi, L.; Cugini, F.; Rosa, R.; Amadè, N. Sarzi; Chicco, S.; Solzi, M.; Veronesi, P.
Abstract: The magnetocaloric Ni50 Mn25 Sn25 Heusler compound was prepared via ultra-fast and sustainable microwave synthesis, by using the two ways hybrid microwave heating method. The structural, microstructural, magnetic and magnetocaloric properties of the prepared specimen are presented. The functional features of the synthetized sample result comparable with compounds obtained with other high-temperature preparation techniques that require larger amount of energy. The proposed time and energy-efficient preparation method could promote the development of large mass production routes of multifunctional huge-potential Heusler compounds, exploitable as active materials in thermomagnetic energy conversion machines and in other technological applications. Graphical abstract: Image, graphical abstract